2019
DOI: 10.1111/jfbc.12886
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and characterization of a new pH‐ and heat‐stable alginate lyase from Pseudoalteromonas carrageenovora ASY5

Abstract: Alginate lyase is important in marine alginate degradation, and its enzymatic hydrolysates are excellent antioxidants. Here, we cloned a new alginate lyase, that is, Alg823, from the Gram‐negative marine bacterium Pseudoalteromonas carrageenovora ASY5. The optimal temperature and pH of Alg823 were 55°C and pH 8.0, respectively. After 30 min of incubation at 50°C, Alg823 could maintain over 75.0% of the maximum enzyme activity, suggesting its thermostability. The recombinant alginate lyase retained more than 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…At the temperature range of 45-55 °C, Aly1281 manifested over 50% of the activity observed at the optimal temperature. Few studies had reported alginate lyases that exhibited optimal reaction temperatures higher than 50 °C, such as AMOR_PL7A (65 °C) [22], cAlyM (55 °C) [23] and Alg823 (55 °C) [5]. The thermostability of Aly1281 was determined at a temperature ranging from 0 °C to 70 °C.…”
Section: Expression Purification and Biochemical Characterization Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…At the temperature range of 45-55 °C, Aly1281 manifested over 50% of the activity observed at the optimal temperature. Few studies had reported alginate lyases that exhibited optimal reaction temperatures higher than 50 °C, such as AMOR_PL7A (65 °C) [22], cAlyM (55 °C) [23] and Alg823 (55 °C) [5]. The thermostability of Aly1281 was determined at a temperature ranging from 0 °C to 70 °C.…”
Section: Expression Purification and Biochemical Characterization Ofmentioning
confidence: 99%
“…Aly1281 exhibited maximum enzyme activity at 50 • C. At the temperature range of 45-55 • C, Aly1281 manifested over 50% of the activity observed at the optimal temperature. Few studies had reported alginate lyases that exhibited optimal reaction temperatures higher than 50 • C, such as AMOR_PL7A (65 • C) [22], cAlyM (55 • C) [23] and Alg823 (55 • C) [5]. The thermostability of Aly1281 was determined at a temperature ranging from 0 • C to 70 • C. As shown in Figure 3B, Aly1281 was relatively stable at temperatures lower than 55 • C. Aly1281 showed competitive thermostability in comparison with most reported marine-derived alginate lyases [15,[24][25][26], which could benefit its industrial application.…”
Section: Expression Purification and Biochemical Characterization Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few of these reported enzymes have been commercially used owing to their poor properties [ 56 ]. Several alginate lyases with certain specific characteristics have been found and studied, such as pH stability [ 51 , 57 ], thermo-tolerance [ 58 ], cold adaption [ 59 , 60 ], acidic or alkaline adaption [ 61 , 62 ], single product distribution [ 63 , 64 ], which are quite significant for both research and commercial purposes, but the enzymes with optimal characteristics are rare. It is worth noting that cold-adapted alginate lyases make running biocatalysis at low temperature possible, which is crucial to reduce the danger of contamination and improve the sustainability of enzyme utilization, thereby decreasing the input costs to some extent, particularly for industrial production of oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%